2020
DOI: 10.1016/j.seizure.2020.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin receptor expression and mTOR pathway activation in glioneuronal tumours of childhood

Abstract: To investigate the expression of somatostatin receptors (SSTRs) and markers of mTOR pathway in paediatric glioneuronal tumours and correlate these findings with tumour type, BRAFV600E mutational status and clinical characteristics such as tumour location, seizure frequency and duration, and age. Method: 37 children and adolescents with a neuropathological diagnosis of glioneuronal tumour were identified over a 22-year period. Immunohistochemical analyses for SSTRs type 1, 2A, 3, 5 and ezrin-radixin-moesin (ERM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 66 publications
(114 reference statements)
0
3
0
Order By: Relevance
“…The antiproliferative effect of SST can be mediated by the five SSTR, according to receptor subtypes and target cells ( 39 , 40 ). In the pituitary gland, SSTR2 and SSTR5 are the most abundantly expressed SSTRs ( 41 ) Here, we demonstrated that SSTa inhibited the proliferative effect induced by FGF2 in lactotroph and somatotroph cells which expressed both receptors. This effect could be mediated by a major contribution of SSTR2, since octreotide has a high affinity for SSTR2 and a low affinity for SSTR5.…”
Section: Discussionmentioning
confidence: 75%
“…The antiproliferative effect of SST can be mediated by the five SSTR, according to receptor subtypes and target cells ( 39 , 40 ). In the pituitary gland, SSTR2 and SSTR5 are the most abundantly expressed SSTRs ( 41 ) Here, we demonstrated that SSTa inhibited the proliferative effect induced by FGF2 in lactotroph and somatotroph cells which expressed both receptors. This effect could be mediated by a major contribution of SSTR2, since octreotide has a high affinity for SSTR2 and a low affinity for SSTR5.…”
Section: Discussionmentioning
confidence: 75%
“…RAS-RAF-MAPK signaling cascade have been described in GG and DNET with BRAF V600E mutations, which were always accompanied by the activation of mTOR signaling cascade with increased phosphorylated ribosomal S6 protein (pS6) (LaSarge and Danzer, 2014;Prabowo et al, 2014;Ehrstedt et al, 2020); in addition, c-MYB/MYBL1, as one of the regulated transcription factors of both signaling cascades, have also been demonstrated in IDG and AG with MYB-QKI fusion (Blümcke et al, 2016;Qaddoumi et al, 2016;Slegers and Blumcke, 2020). Particularly, the MAP kinase activation can be regulated by substrates of the PI3K-AKT-mTOR signaling cascade and vice versa, which have been identified as more related to focal malformations of cortical development (MCD), such as tuberous sclerosis complex (TSC), hemimegalencephaly, and FCD (Crino, 2015;Pernice et al, 2016).…”
Section: Genetic Alterations In Mvntmentioning
confidence: 99%
“…In summary, genetic alterations detected in LEAT entities involve and connect two major signaling pathways, namely, the mitogen-activated protein kinase (MAPK) pathway and the mammalian target of rapamycin (mTOR) pathway ( Figure 1 ; Blümcke et al, 2016 ; Pernice et al, 2016 ; Delev et al, 2020 ). For example, FGFR1 as receptor signaling at upstream of both pathways has been identified in DNETs with FGFR1 alterations; BRAF as a substrate further downstream of the RAS-RAF-MAPK signaling cascade have been described in GG and DNET with BRAF V600E mutations, which were always accompanied by the activation of mTOR signaling cascade with increased phosphorylated ribosomal S6 protein (pS6) ( LaSarge and Danzer, 2014 ; Prabowo et al, 2014 ; Ehrstedt et al, 2020 ); in addition, c-MYB/MYBL1, as one of the regulated transcription factors of both signaling cascades, have also been demonstrated in IDG and AG with MYB-QKI fusion ( Blümcke et al, 2016 ; Qaddoumi et al, 2016 ; Slegers and Blumcke, 2020 ). Particularly, the MAP kinase activation can be regulated by substrates of the PI3K-AKT-mTOR signaling cascade and vice versa, which have been identified as more related to focal malformations of cortical development (MCD), such as tuberous sclerosis complex (TSC), hemimegalencephaly, and FCD ( Crino, 2015 ; Pernice et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%